The Effect of Rev-erbα Agonist SR9011 on the Immune Response and Cell Metabolism of Microglia - Wolff, Samantha E. C.; Wang, Xiao-Lan; Jiao, Han; Sun, Jia; Kalsbeek, Andries; Yi, Chun-Xia; Gao, Yuanqing (Frontiers in Immunology, 2020)
Microglia are the immune cells of the brain. Hyperactivation of microglia contributes to the pathology of metabolic and neuroinflammatory diseases. Evidence has emerged that links the circadian clock, cellular metabolism and immune activity in microglia. Rev-erbα nuclear receptors are known for their regulatory role in both the molecular clock and cell metabolism, and have recently been found to play an important role in neuroinflammation. The Rev-erbα agonist SR9011 disrupts circadian rhythm by altering intracellular clock machinery. However, the exact role of Rev-erbα in microglial immunometabolism remains to be elucidated. In the current study, we explored whether SR9011 also had such a detrimental impact on microglial immunometabolic functions. Primary microglia were isolated from 1-3 days old Sprague-Dawley rat pups. The expression of clock genes, cytokines and metabolic genes was evaluated using RT-PCR and rhythmic expression was analyzed with JTK_Cycle. Phagocytic activity was determined by the uptake capacity of fluorescent microspheres. Mitochondria function was evaluated by measuring oxygen consumption rate and extracellular acidification rate with the Seahorse XFe96 Analyzer. We found that key cytokines and metabolic genes are rhythmically expressed in microglia. SR9011 disturbed rhythmic expression of clock genes in microglia. Pro-inflammatory cytokine expression was attenuated by SR9011 during an immune challenge by TNFα, while expression of the anti-inflammatory cytokine Il10 was stimulated. Moreover, SR9011 decreased phagocytic activity, mitochondrial respiration, ATP production, and metabolic gene expression. Our study highlights the link between the intrinsic clock and immunometabolism of microglia. We show that Rev-erbα is implicated in both metabolic homeostasis and the inflammatory responses in microglia, which has important implications for the treatment of metabolic and neuroinflammatory diseases.